2015
DOI: 10.11622/smedj.2015123
|View full text |Cite
|
Sign up to set email alerts
|

Infant lumbar and thoracic epidurals for abdominal surgeries: cases in a paediatric tertiary institution

Abstract: INTRODUCTIONThere is strong evidence that epidural analgesia provides good postoperative pain relief in adults, but its use in infants is less established. In this retrospective study, we present our experience with managing infant epidural analgesia for abdominal surgeries in a tertiary paediatric institution. METHODSThe records of 54 infants who had received a thoracic or lumbar epidural as perioperative analgesia for abdominal surgeries were included. The mean age of the infants was 6.1 (standard deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
(12 reference statements)
0
9
1
1
Order By: Relevance
“…Indeed, many centers routinely perform TEA in this setting, reporting successful IE rate in up to 80% of children. 4,7 Similarly, IE after pediatric liver transplantation has been considered a primary goal by many anesthesiologists, and a satisfactory IE rate has been achieved in some specialized pediatric liver centers, [10][11][12]25,26 ranging from 40% to more than 70%. Ulukaya et al 13 were the first to report IE in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, many centers routinely perform TEA in this setting, reporting successful IE rate in up to 80% of children. 4,7 Similarly, IE after pediatric liver transplantation has been considered a primary goal by many anesthesiologists, and a satisfactory IE rate has been achieved in some specialized pediatric liver centers, [10][11][12]25,26 ranging from 40% to more than 70%. Ulukaya et al 13 were the first to report IE in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Thong et al 4 in a large retrospective series of children undergoing major abdominal procedures (but not transplants) have shown that TEA is safe and effective, with a very small number of complications. Indeed, many centers routinely perform TEA in this setting, reporting successful IE rate in up to 80% of children 4,7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Las complicaciones más frecuentes fueron problemas técnicos (12,7% de los pacientes) tales como retiro accidental del catéter, filtración de anestésico local y oclusión del catéter, las cuales determinaron el término precoz de la analgesia peridural. Estos resultados concuerdan con estudios recientes, los cuales señalan que las principales complicaciones asociadas a catéteres peridurales lumbares y torácicos fueron la desconexión, la filtración y la obstrucción (Thong et al, 2015;Walker et al, 2018). En los pacientes en los cuales hubo retiro accidental del catéter, la reinstalación de la analgesia peridural no fue realizada y ésta fue administrada de forma endovenosa mediante paracetamol y/o ketorolaco.…”
Section: Díaunclassified